Perspectives of Virtual Exchange in Algerian EFL Instruction: Facing the Digital Divide - Ghofrane AMAIDIA (My University, 2022)
Abstract The current study aimed to explore the different perspectives held on the use of virtual exchange (VE) in the Algerian EFL instruction. Additionally, it sought to investigate the effectiveness of using virtual exchange in enhancing Algerian EFL students' learning and fostering their intercultural communicative competence which enables them to face and overcome the digital divide. Aiming to test the main hypotheses, the researcher opted for four instruments; a questionnaire for teachers, a questionnaire for master one and third-year students, a participant observation because the researcher was immersed in the day-to-day activities done in a VE project called "On the Other Side of the World" initiated by Mohamed-Cherif Messaadia University and Constantine the Philosopher University of Slovakia, and a post-project questionnaire addressed to participants of the project. The gathered data have illustrated that VE has a positive impacts on Algerian EFL students' learning; it developed their language skills, enhanced the intercultural communicative competence, and enlarged their digital literacy. Based on these results, raised hypotheses were confirmed. --------------- ملخص يكمن الهدف الرئيسي من هذه الدراسة في تقصي وجهات النظر التي يحملها البعض تجاه استعمال التبادل الافتراضي اثناء تدريس الانجليزية كلغة أجنبية في الجزائر. كما تهدف هذه الدراسة إلى التحقق من مدى فعالية التبادل الافتراضي في تحسين تعليم الطلاب و تطوير كفاءتهم في التواصل عبر الثقافات و التي بإمكانها ان تساهم في مواجهة الفجوة الرقمية و تضييقها. من أجل تحقيق الاهداف المذكرة أعلاه، بدأ الباحث بتجميع البيانات المرادة ثم حلّلها ليستخلص منها بعد ذلك بعض الاقتراحات و النتائج التي من شأنها أن تؤدي الى إدماج هذا الأخير في تعليم الإنجليزية كلغة أجنبية. كما أشارت النتائج المتوصل اليها أنّ التبادل الافتراضي فائق الأهمية في تطوير كفاءات الطلاب و قدراتهم ---------------------- Résumé L'objectif de cette étude est d'examiner les perspectives et les points de vues maintenues sur l'utilisation d'échange virtuel dans l'enseignement algérien de l'anglais comme langue étrangères. De plus, elle tente d'explorer les effets de l'usage d'échange virtuel sur l'amélioration de l'apprentissage et la promotion de la compétence communicative interculturelle pour faire face le fossé numérique. Pour réaliser les objectifs précités, le chercheur a recueilli les données nécessaires, les a analysées, puis il/elle a fait des conclusions. Les résultats ont révélé que l'échange virtuel est primordial pour développer et augmenter les compétences des étudiants